The Influence of Problem Based Learning (PBL)-Based Student Worksheets on Sustainable Development Goals (SDGs) to Improve Students’ Critical Thinking Skills - Yonanda, Hanny Dwi; Istiana, Rita; Prasaja, Dimas (Journal Of Biology Education Research (JBER), 2023)
The development of 21st century science and technology in the field of education requires students to be able to master the 4C skills, one of which is critical thinking. Critical thinking skills can improve students' ability to solve problems, draw conclusions and find appropriate solutions from various aspects and perspectives they will face. PBL-based student worksheets and PBL learning models are the right choice to improve critical thinking skills and can be linked to SDGs problems which will later make students solve various problems to be able to achieve SDGs goals and targets. This study aims to analyze the improvement in aspects of students' critical thinking skills after applying PBL-based student worksheets on SDGs problems. The research was conducted at a public high school in Bogor Regency, while the method used was a experiment. The population that was used as the object of research was students in several public high school classes in Bogor Regency, with cluster random sampling taking the sample. Based on the results of research and analysis, it shows that PBL-based student worksheets can improve students' critical thinking skills in SDGs problems, seen from the N-Gain score in the experimental class of 0.48 and the control class 0.32 in the medium category. The activeness of the students in the class which was assessed through the attitude and skill aspects, showed that the experimental class was higher than the control class which affected the improvement of students' critical thinking skills. The conclusion of this research is that the alternative research hypothesis is accepted, so that there is an influence of PBL-based student worksheets on SDGs issues to improve students' critical thinking skills.